Electrospinning of boron nitride nanofibers with high temperature stability. (September 2019) - Liu, Zhaowei; Zhao, Kang; Luo, Jing; Tang, Yufei
Abstract: A complex synthesized by boric acid and melamine was used as a precursor, and continuous BN nanofibers were obtained by electrospinning, followed by low-temperature calcination in air and high-temperature calcination in nitrogen. The nanofibers contained a low impurity with the atomic content of O was only 5.36%. With the specific surface area of about 512m 2 /g, the onset temperature of oxidation was as high as 920 °C due to a long axis ratio and a parallel arrangement of the crystal planes in the fiber axis. The obtained BN nanofibers have broad application value in the fields of aerospace and high temperature filtration. Graphical abstract: Unlabelled Image